PENYULUHAN GIZI SEIMBANG DAN BAHAYA PENGGUNAAN GADJET PADA ANAK-ANAK TK MELATI ASRI DI KOTA BANDUNG - Ria Khoirunnisa Apriyani; Desy Puspa Rahayu; Nita Rustanti; Nuke Dewi Utami Hamid (ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
Melati Asri Kindergarten in Bandung City has several problems. Among them are (1) Lack of knowledge related to nutritional information and the use of gadgets as children's activities that have an impact on children's growth and development. (2) Lack of information about dissemination on balanced nutrition and the negative impact of using gadgets in the local environment. This PKM activity aims to provide information to increase knowledge of parents of Melati Asri students regarding the fulfillment of balanced nutritional intake and the dangers of using gadgets in children. This PKM used counseling with acceleration learning patterns, lectures, discussions, questions and answers, and presentation using visual media as a method. This PKM activity received a positive response from the parents, which was shown by the enthusiasm of the parents during the Q&A session.